2004
DOI: 10.1074/jbc.m402148200
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution Exerted by AF-1 and AF-2 Transactivation Functions in Estrogen Receptor α Transcriptional Activity Depends upon the Differentiation Stage of the Cell

Abstract: The activity of the transactivation functions (activation function (AF)-1 and AF-2) of the estrogen receptor ␣ (ER␣) is cell-specific. This study aimed to decipher the yet unclear mechanisms involved in this differential cell sensitivity, with particular attention to the specific influence that cell differentiation may have on these processes. Hence, we comparatively evaluated the permissiveness of cells to either ER␣ AFs in two different cases: (i) a series of cell lines originating from a common tissue, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 51 publications
5
93
0
Order By: Relevance
“…3A). A dose-response curve established using MCF-7 (and MDA-66, see below) cells has indicated that, as also reported by others, a concentration of 10 nM E2 was the optimal ligand concentration to be used for the highest level of pS2 gene induction in mammary cells cultured in vitro (results not shown, see [18,19]). Therefore, whenever we studied the effects of E2 we have added this ligand to cell culture medium at a 10 nM concentration.…”
Section: Ectopic Era Expression In Mda-mb-231 Upregulates Nis Expressionsupporting
confidence: 60%
See 2 more Smart Citations
“…3A). A dose-response curve established using MCF-7 (and MDA-66, see below) cells has indicated that, as also reported by others, a concentration of 10 nM E2 was the optimal ligand concentration to be used for the highest level of pS2 gene induction in mammary cells cultured in vitro (results not shown, see [18,19]). Therefore, whenever we studied the effects of E2 we have added this ligand to cell culture medium at a 10 nM concentration.…”
Section: Ectopic Era Expression In Mda-mb-231 Upregulates Nis Expressionsupporting
confidence: 60%
“…3). Concerning the differences between cell lines, we must point out that, when compared to MCF-7, MDA-MB-231 (or MDA-66) cells are less differentiated, and it is known that the differentiation stage of breast cancer cell lines strongly affects the transcriptional activity of nuclear receptors [18]. In parallel to this, our results suggest that in addition to functionally expressed RARa and ERa, (an)other so far unidentified factor(s) are (is) essential for ligand-responsive expression of this gene in MDA-MB-231.…”
Section: Ectopic Era Expression In Mda-mb-231 Upregulates Nis Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations can be correlated to the capacity of ERα, but not of ERβ, to recruit NCOA1 via its AF1 region in the presence of tamoxifen (Webb et al . 1998, Merot et al . 2004).…”
Section: Impact Of Ae-induced Erα Conformation On Cofactor Recruitmenmentioning
confidence: 99%
“…Specifically, only ϳ20% of all genes regulated through either ER isoform are regulated by both ER isoforms. The mechanism(s) of ER isoform-specific gene regulation are unknown; however because of the low level of homology between the ER␣ and ER␤ A/B (AF1) domains, differences in transcriptional activation may be largely due to AF1 function (30,31).In this study, we show that the RBBP1 gene, the protein product of which is involved in retinoblastoma-mediated suppression of cell proliferation, is differentially regulated by ER␣ and ER␤ in a U2OS model system. Using deletion and mutational analysis, we demonstrate that ER␣ utilizes a consensus Sp1 sequence, whereas ER␤ functions through both the Sp1 and a nearby ERE sequence.…”
mentioning
confidence: 99%